(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2020)
This research is motivated by the high number of child marriages in South Kalimantan which reached 51 / 1,000 population in 2010 and 2016 which exceeded the national average, which is 40 / 1,000 population. In 2017 there has been no significant change in numbers. One of the root causes of child marriage is the values of Banjar that shape the behavior of child marriage. These values need to be studied in the form of research. Through the descriptive-qualitative method, this study took 7 sample districts, each consisting of 5 respondents. Data collection uses snowball technique, observation and interviews. The analysis was carried out qualitatively based on the theory of ethics and Banjar values. The following findings. First, the Banjar values which form the basis of child marriage are given 3 main values, namely the value of harmony, economic value and religious value, which are all interrelated in determining how to marry a child. Second, efforts to achieve value have not been carried out optimally. Third, generally child marriage companions do not get assistance that is not important to change the culture of child marriage.